A errância como potência em Dom Quixote - Pedrosa, Gabriel (2019)
From Don Quixote's refusal to seek courts or cities, made explicit in a dialogue with Sancho Panza in the twentieth-first chapter of the first part of Cervantes's book, this article reflects on his wandering, as a perambulation in the fields, but also as a non-function-oriented behavior and as an identity in constant invention. This reflection, with the various philosophical and literary references that it raises, finds not a peculiarity of the knight from la Mancha, but a permanent tension in our culture, proposing Don Quixote as a reversion of the way we are used to read it.